Analysis of the Influence of Product and promotion On Purchase Decisions on the Products of Micro, Small and Medium enterprises in the District Rengat - Hermanto; Roky Apriansyah; Yudha Remofa (International Journal of Science, Technology & Management, 2021)
This research was conducted on Micro, Small and Medium enterprises engaged in the business of Chips Onion/Banana Kecamatan Rengat. The sample in this research is consumers who shop at the business Chips Onion/Banana Kecamatan Rengat as many as 99 Samples. The type of data used in this research is primary data in the form of quantitative data was done by distributing questionnaires messages to consumers who shop. Analysis tools that the authors use is Multiple Linear Regression Analysis with a quantitative approach with the help of SPSS Software Version 21. The results of the research can be concluded that : (1) the Product is partially significant effect on Purchase Decisions on SMES in the district Rengat. (2) the Promotion is partially significant effect on SMES in the district Rengat. (3) Products and Promotions simultaneously have a significant effect on Purchase Decisions on SMES in the district Rengat.